Pseudocapacitive Charge Storage at Nanoscale Silicon Electrodes. (13th April 2015) - McSweeney, William; Geaney, Hugh; Glynn, Colm; McNulty, David; O'Dwyer, Colm
Abstract : Pseudocapacitive behaviour can be accessed when Si nanowire (NW) electrodes are scanned at relatively fast potential scan rates in Li-ion battery electrolytes. Measurements using cyclic voltammetry supported by electron microscopy confirm that Si NWs formed on silicon substrates, as opposed to metallic current collectors, do not solely undergo alloying reactions. The influence of doping type, carrier concentration and bias condition during voltammetric polarization significantly alters the mechanism of electrochemical energy storage. The formation of a carrier depleted (electrically dead) layer of n-type NWs on silicon current collector electrodes limits insertion or alloying processes and rates that ordinarily form Li-Si phases, and charge is also stored within the electric double layer via pseudocapacitive processes. P-type NWs with solid crystalline cores also exhibit pseudocapacitive charge storage without structural modification of the NWs.